Odstąpienie od wymierzenia kary lub środka karnego za przestępstwa skarbowe - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article is a theoretical study of waiving the penalty of a fiscal penal law violator. The issues addressed in the article present major problems that draw attention of the theorists and practicioners alike in the field. The aim of the article is to evaluate the contemporary model of penalty waiver that is formulated by the Fiscal Penal Code. The author analyses in detail the institution described in the Fiscal Penal Code, Chapter 2: penalty waiver. The study ends with closing remarks, including general conclusions and assumptions that relate to the model of penalty waiver.
Keywords: waiving the penalty; fiscal penal law; fiscal penal law violator; model of penalty waiver; Fiscal Penal Code